Evidence of Pliocene-Pleistocene Unconformity in eastern Bogor Trough, Sumedang-West Java - Alam, Syaiful; Sendjadja, Yoga Andriana; Jurnaliah, Lia; Fachrudin, Kurnia Arfiansyah; Gani, Reza Mohammad Ganjar (Faculty of Geological Engineering, Universitas Padjadjaran, 2019)
AbstractRecent measuring stratigraphic observation in Cikandung River has revealed the Late Pliocene stratigraphic and tectonic event. Research area is located in easter Bogor Trough. Previously, it was stated controversially pertaining to the stratigraphic relationship between Kaliwangu and Citalang Formations. The outcrop-based remark has never been explained, slightly intuitive. Making strike and dip measurements and stratigraphic analysis using tape and compass traverse were done to unveil the role of Plio-Pleistocene tectonic regime in stratigraphic-filling of the basin. Strike azimuths recorded from several locations of Citalang and Kaliwangu Formations show angular geometry and both of those sedimentary facies within formations indicate the significant and rapid change in depositional process. But interestingly, the angular geometry is only founded in the southern part of study area. To the north, angular relationship becomes parallel. This geometrical distribution implies the strong influence of tectonic regime in Late Pliocene interval. The evidence from outcrops observation conclude the unconformity between Citalang and Kaliwangu Formations. Keywords: Stratigraphic unconformity, Citalang and Kaliwangu Formations, Plio Pleistocene Tectonic